2014
DOI: 10.1016/j.jcin.2014.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Revascularization for Multivessel Coronary Artery Disease

Abstract: HCR is feasible in select patients with MVCAD referred for conventional CABG. (Safety and Efficacy Study of Hybrid Revascularization in Multivessel Coronary Artery Disease [POL-MIDES]; NCT01035567).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(99 citation statements)
references
References 17 publications
8
81
0
8
Order By: Relevance
“…Due to the difficulty in implementing a randomized controlled study on surgical patients, all except one (Gasior 2014) are observational studies. 11 These newer studies were performed either as a single-or double-staged HCR, and the approach varied from median sternotomy to robot-assisted endoscopic atraumatic CABG with or without CPB assistance. Drug-eluting stents were used in most of the patients.…”
Section: Mics Hcr One-stage Hcr: Cabg-pci Hcr: Pci-cabgmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the difficulty in implementing a randomized controlled study on surgical patients, all except one (Gasior 2014) are observational studies. 11 These newer studies were performed either as a single-or double-staged HCR, and the approach varied from median sternotomy to robot-assisted endoscopic atraumatic CABG with or without CPB assistance. Drug-eluting stents were used in most of the patients.…”
Section: Mics Hcr One-stage Hcr: Cabg-pci Hcr: Pci-cabgmentioning
confidence: 99%
“…20 The reported stroke rates were 0% to 1.7%. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] It is notable that despite the anaortic approach used for the HCR CABG arm (mostly in situ LIMA conduit), the stroke rates are not much lower.There are two meta-analyses that evaluate the studies done on HCR and conventional CABG patients (Table 2). 27,28 Phan and Harskamp both showed that there is no benefit for perioperative mortality, stroke, or 1-year freedom from major adverse events when using HCR over CABG.…”
mentioning
confidence: 99%
“…The first, the POL-MIDES study, compared HCR to conventional CABG in 200 patients (22). In this study, no significant differences were seen in death, myocardial infarction, stroke, major bleeding, or repeat revascularization at 1-year (MACCE 11% vs. 8%).…”
Section: Randomized Datamentioning
confidence: 91%
“…El primer estudio prospectivo y aleatorizado sobre RMH fue publicado por Gasior et al, en 2014 23 . Los autores hacían hincapié en las limitaciones de la CRM convencional y los resultados no satisfactorios a largo plazo de los injertos venosos para justificar la aleatorización a CRM o RMH.…”
Section: Los Estudiosunclassified